2024
DOI: 10.2319/081823-567.1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of root resorption associated with the use of photobiomodulation during orthodontic treatment with clear aligners: a retrospective cohort pilot study

Antonio Rossi,
Manuel Lagravère-Vich,
Giseon Heo
et al.

Abstract: Objectives To evaluate the change in tooth root volume using cone-beam computed tomography (CBCT) in a group of patients treated concurrently with clear aligners and an adjunctive photobiomodulation (PBM) device. Materials and Methods This retrospective cohort pilot study included the records of 32 consecutively treated clear aligner patients (23 female, 9 male) from the private practice of one orthodontist. The PBM group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In related research, Rossi et al [40] explored the impact of PBM on root resorption in orthodontic patients using clear aligners, with no notable difference in root resorption observed between the group using PBM and the control group. This outcome suggests that PBM's adjunctive application in orthodontic treatments using clear aligners does not escalate the risk of orthodontically induced external root resorption; however, caution is advised when interpreting these results due to the limited sample size and possible measurement inaccuracies [40]. Olek et al [41] also reported that photodynamic therapy could decrease microbial levels in patients with fixed orthodontic appliances, presenting a viable alternative to traditional periodontal maintenance practices [41].…”
Section: Safety Of Low-level Laser In Accelerated Orthodonticsmentioning
confidence: 99%
See 4 more Smart Citations
“…In related research, Rossi et al [40] explored the impact of PBM on root resorption in orthodontic patients using clear aligners, with no notable difference in root resorption observed between the group using PBM and the control group. This outcome suggests that PBM's adjunctive application in orthodontic treatments using clear aligners does not escalate the risk of orthodontically induced external root resorption; however, caution is advised when interpreting these results due to the limited sample size and possible measurement inaccuracies [40]. Olek et al [41] also reported that photodynamic therapy could decrease microbial levels in patients with fixed orthodontic appliances, presenting a viable alternative to traditional periodontal maintenance practices [41].…”
Section: Safety Of Low-level Laser In Accelerated Orthodonticsmentioning
confidence: 99%
“…The non-invasive nature of PBM is one of its most notable advantages, eliminating the need for surgical interventions, thereby reducing the risk of complications [39]. This aspect alone makes PBM a safer choice, especially when compared to methods that involve electrical stimulation in moist environments [38][39][40][41]. Additionally, PBM's precision in action and control, facilitated by the use of specific wavelengths tailored to individual treatment plans, enhances its safety profile and effectiveness [38][39][40][41].…”
Section: Advantages Of Photobiomodulation In Orthodontic Treatmentmentioning
confidence: 99%
See 3 more Smart Citations